Detection of Carbohydrate Compounds in Compost Made From Soybean Husk and Cow Manure - Mursiani, Sri (Journal of Tropical Crop Science and Technology, 2021)
Husk through composting techniques. However, information about the characteristics of soybean husk still needed to be studied more deeply. This caused coagulation of primary metabolites which had a very important biological functions as an energy source, fuel and intermediates for planting, the formation of RNA and DNA structural work (ribonucleic acid and deoxyribonucleic acid), this could be used to help explore the profile carried out in soybean husk degradation. Detection of carbohydrate compounds in this study used Gas Chromatography–Mass Spectroscopy (GC–MS) because it was a powerful tool in characterizing compost. The purpose of this study was to detect carbohydrate compounds in compost made from soybean husk and cow manure. Thus, further information obtained could be used as recommendations in handling soybean husk, especially as organic fertilizer through composting techniques.The study was conducted using a Randomized Complete Block Design (RCBD) with 5 composting arrangements with five replications. Related to payments were: C1: soybean husk (100 %), C2: cow manure (100 %), C3: soybean husk: cow manure (50 %: 50 %), C4: soybean husk: cow manure (75 %: 25 %) and C5: soybean husk: cow manure (25 %: 75 %). Data were analyzed using GC–MS and Least Significant Difference (LSD). Based on analysis using GC–\MS on compost, six sugar compounds were detected. While the treatment that showed the highest area of the curve was C5 (25 % soybean husk: 75 % cow manure), this result was directly proportional to the Least Significant Difference (LSD).